Social norms and physical activity in American and Canadian contexts: a scoping review. Issue 1 (1st January 2019) - Kim, Jeemin; Dunn, Emily; Rellinger, Kayla; Robertson-Wilson, Jennifer; Eys, Mark
ABSTRACT: Social norms are unwritten rules about how to behave in a group, and have been shown to impact health behaviour change. There are equivocal findings regarding social norms in the context of physical activity, which may be attributed to inconsistencies in their conceptualization and measurement. This scoping review explored the literature examining social norms as they relate to physical activity, with an emphasis on how researchers have conceptualized and measured social norms. A total of 137 articles were reviewed. The majority ( n  = 125, 91%) were grounded within the theory of planned behaviour (TPB) and varied considerably in their conceptualization and measurement of subjective norms. Studies not grounded within the TPB either measured ( n  = 5, 4%) or manipulated ( n  = 7, 5%) injunctive and descriptive norms. These results also allowed for the identification of future research considerations, including potential covariates (e.g. social support) and moderators (e.g. personality characteristics) that may help explain the equivocal findings regarding the role of subjective norms in promoting physical activity. Overall, the current review highlights several aspects that future researchers may consider when examining social norms and/or designing interventions for physical activity based on normative influences.